Impact of Transaction Costs on Mediums of Exchange - Malinovský, Daniel; Teplý, Petr, 1977-; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
In this thesis, we present our theoretical model on the various levels of liquidity of individual forms of money. Specifically, we connect Coase's transaction costs economics applied on money forms through history together with Keynes' preference of liquidity in order to explain how transaction costs impact the selection of which money form is used as a medium of exchange. By testing two hypotheses, we came to the following conclusions, 1. money forms are imperfect and are limited in their innovation and, 2. transaction costs have an impact on the liquidity of the money form. We show that each money form has an innovation limit that cannot be overcome by design. Comparative analysis is employed to identify trends in transaction costs of the individual forms of money. Each newer money form is linked to lower transaction costs and thus higher liquidity. High liquidity money forms with lower transaction costs then push low liquidity money forms out of circulation through a process called "monetary extrusion." Furthermore, attention is given to individual consumer preferences in transaction costs which serve as an explanation of the different preferences of money forms among consumers. Our results show important policy implications for regulators regarding consumers' varying preferences. With these implications come additional considerations that regulators should take into account while making a cost-benefit analysis of CBDC implementation. Among these considerations are the amount of trust between central banks and consumers, cashless adoption, and privacy concerns.
Vedoucí práce: Petr Teplý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses